Abnormalities of mucosal serotonin metabolism and 5-HT3 receptor subunit 3C polymorphism in irritable bowel syndrome with diarrhoea predict responsiveness to ondansetron - Gunn, David; Niesler, Beate (Alimentary pharmacology & therapeutics, 2019)
Background: Irritable bowel syndrome with diarrhoea (IBS-D) is a common condition, greatly reducing the quality of life with few effective treatment options available. Aim: To report the beneficial response shown in our trial with the 5-hydroyxtryptamine (5-HT) receptor 3 antagonist, ondansetron in IBS-D. Methods: A randomised, placebo-controlled, cross-over trial of 5 weeks of ondansetron versus placebo in 125 patients meeting modified Rome III criteria for IBS-D as previously described. Patients were compared to 21 healthy controls. 5-HT and 5-HIAA were measured in rectal biopsies. Whole gut transit time was assessed using a radio-opaque marker technique. Whole blood DNA was genotyped for an insertion polymorphism in the promoter region of the serotonin transporter gene SLC6A4, as well as single nucleotide polymorphisms (SNPs) of the tryptophan hydroxylase gene TPH1 and 5-HT3 receptor genes HTR3A, C and E. Results: Patients’ biopsies showed significantly higher 5-HIAA levels (2.1 (1.2-4.2) pmol/mg protein vs 1.1 (0.4-1.5) in controls, P < .0001). 39 patients used < 4 mg/d (“super-responders”) while 55 required ≥ 4 mg/d. 5-HT concentrations in rectal biopsies were significantly lower in super-responders (21.3 (17.0-31.8) vs 37.7 (21.4-61.4), P = .0357) and the increase in transit time on ondansetron was significantly greater (15.6 (1.8-31) hours vs 3.9 (−5.1-17.9) hours). Stool consistency responders were more likely to carry the CC genotype of the SNP p.N163K rs6766410 of the HTR3C gene (33% vs 14%, P = .0066). Conclusion: IBS-D patients have significant abnormalities in mucosal 5-HT metabolism. Those with the lowest concentration of 5-HT in rectal biopsies showed the greatest responsiveness to ondansetron.